Analysis of the influence of amplitude, frequency, angle of propagation, and air pressure on the characteristics of sound waves - Setya, Winda; Azmi, Ilman; Istiqomah, Ikmal Konit; Aditya, Dinaldhi Muhammad; Chusni, Muhammad Minan; Mahen, Ea Cahya Septia; Pitriana, Pina; Nuryantini, Ade Yeti; Susanti, Seni (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2025)
This study offers a comprehensive approach that has not been widely explored, integrating PhET interactive simulations and the Phyphox sensor application to analyze the simultaneous influence of four physical parameters amplitude, frequency, dispersion angle, and pressure on the characteristics of sound waves. The integration of PhET interactive simulations and the Phyphox application enables real-time visualization and experimental data measurement through smartphone sensors. Furthermore, this research contributes new insights by exploring the dispersion angle in the context of wave direction and intensity, a topic rarely discussed in digital media-based acoustic studies. The method used is a quantitative experiment with amplitude variations from 1 to 10 and frequencies of 400 Hz, 500 Hz, and 600 Hz, measured at distances of 1 cm, 3.25 cm, and 5.5 cm. The study also includes observations of reflection and interference patterns of waves at propagation angles of 18°, 45°, and 90°, as well as an analysis of the effect of air pressure on sound intensity, with pressure varied from 0.0 atm to 1.0 atm. The results show that sound wave intensity increases with higher amplitude and frequency, in accordance with the theory that intensity is proportional to the square of the amplitude. The propagation angle influences the reflection and interference patterns, resulting in varied energy distribution. Additionally, air pressure significantly affects sound intensity, emphasizing the crucial role of the medium in sound wave propagation.